(untitled) (LEARNing Landscapes, 2009)
In this qualitative study I explored six college (CEGEP) teachers’ perspectives on teaching and learning over a two-year period, as they completed the first four courses in a professional development program, the Master Teacher Program (MTP). Repeated, semi-structured interviews were analyzed, using the complementary processes of categorizing and connecting. Results revealed, through four patterns and three major dimensions, a process of evolution from a teacher- to a learner-centered perspective.